ANALISIS PANDANGAN PENDIDIKAN SERTA PARTISIPASI POLITIK PADA PILKADA KABUPATEN BADUNG - Sihombing, Immanuel Pratama; Erviantono, Tedi; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2023)
Education is a right for all people in Indonesia which makes the next government responsible for the implementation of free education in their respective region. Indonesia is the third largest democracy after India and the United States. As one of the democratic countries in the world, the Indonesian state in determining state leaders, both those who sit in the executive and legislative institutions, uses an electroral system. Political recruitment organized by political parties gives freedom to all citizens who meet the requirements to participate in making choices in general elections based on the principle of direct public freedom and secrecy, as well as honesty and fairness. Keyword: Badung Regency, Politic Education, Politic Participation, Election.